ANALYSIS OF READING COMPREHENSION OF ENGLISH NARRATION OF THE ENGLISH STUDENTS OF MUHAMMADIYAH UNIVERSITY OF SURAKARTA IN THE ACADEMIC YEARS 2006/2007 - ANGGRAENI, DIAN PUSPITA (2007)
This study is aimed (1) to describe students' ability in (a) finding the main idea, (b) identifying technique of the paragraph development, and (c) inferring the message of each short story on "A Man Who Never Gives Up" written by Nasreddin, retold by Sugeng Haryanto in the students of Muhammadiyah University the Academic Years 2006/2007, (2) to describe the difficulties of students in comprehending English narration of the short story on A Man Who Never Gives Up. This is the qualitative research. In this research, the writer gathers the data by using a test. The writer finds that: (a) the students who can answer correctly the questions related with the main idea are only 61,4 % So, there are 38,6 % of students still can not find the main idea of the paragraph, (b) the students who can answer the questions related paragraph development are only 53,9%, so there are 46,1 % students still answers incorrectly and (c) the students who can answer the questions related to infer the message are 78,9 %, so there are 21,1 % students still answers incorrectly. There are five the most difficulties of students in comprehending English narration, they are: (a) understanding about paragraph development, (b) understanding the place of topic sentence, (c) understanding the vocabulary of the story, (d) making accurate prediction, and (e) making restatement of the idea of some paragraph.